Objective measures of design typicality. (January 2018) - Mayer, Stefan; Landwehr, Jan R.
Abstract : Design typicality shapes consumers' aesthetic product preferences. Hence, methods for assessing a product design's typicality are vital to enable predictions of a design's market potential. In this research, we introduce four objective measures of design typicality (two based on Euclidian distances between feature points and two based on pixel-wise image correlations) and demonstrate their capability of capturing a subjective typicality experience. Furthermore, we validate the measures in the context of automobile designs with consumer ratings of aesthetic liking and experienced processing fluency by analysing 77 car models from four segments. Our findings identify the most promising approach to quantify design typicality and endorse the use of this measure in future scientific research and in managing product design in business practice. Highlights: Design typicality significantly predicts aesthetic liking for cars. Design typicality can be measured by fully algorithmic measures. The experience of processing fluency marginally mediates the effect of typicality. Subjective measures of typicality are superior when examining mental processes. Objective measures of typicality are recommended for econometric analyses.